AIRBORNE PIPE WIND TURBINE DESIGN FOR DISADVANTAGED, OUTERMOST, AND FRONTIER AREAS IN INDONESIA - Dzikri Khusaini, Reza
Indonesia is a country that has a large potential of renewable energy. One of the abundant renewable energy sources in Indonesia is wind energy which has a potential of about 950 MW which spreads across several locations in Indonesia. However until now, only 75 MW has been used as a power plant. In this research, the design process of an airborne pipe wind turbine was carried out which is expected to be used to increase the utilization of wind energy in Indonesia. The wind turbine is designed to be able to capture high altitude wind potential in 3T (Disadvantaged, Outermost and Frontier) areas in Indonesia. Wind turbine blades are made using a tube (pipe), therefore the manufacturing process is relatively easier when compared to manufacturing turbine blades in general. To capture wind potential at high altitude, a turbine airborne system using parafoil, rope, and pulley is used. CFD simulations were carried out to obtain the geometry of the pipe wind turbine and parafoil that produces the most optimum performance. From this research, a combination of wind turbine with pipe as blades that has a diameter of 4 meters and airborne wind turbine with air-ram parafoil using NACA 0012 airfoil profile was obtained. This wind turbine can be operated at a high altitude (more than 100 meters) with a maximum power coefficient value of 0.132 at the tip speed ratio of 6.67.